New Rough Approximations Based on E-Neighborhoods - Tareq M. Al-shami; Wen Qing Fu; E. A. Abo-Tabl (Complexity)
This paper puts forward some rough approximations which are motivated from topology. Given a subset R⊆U×U, we can use 8 types of E-neighborhoods to construct approximations of an arbitrary X⊆U on the one hand. On the other hand, we can also construct approximations relying on a topology which is induced by an E-neighborhood. Properties of these approximations and relationships between them are studied. For convenience of use, we also give some useful and easy-to-understand examples and make a comparison between our approximations and those in the published literature.